Comparison of CMV pp65 Antigen and IgM Antibody Detection for Early Recognition of CMV Primary Infection and Reactivation - Jahan, M; Tabassum, S; Islam, MN (Mymensingh Medical Journal, 2008)
Mymensingh Med J. 2008 Jan;17(1):28-31. The abstract of this article is available on the PubMed website